Pediatric Electrical Bicycle Road Accidents - Avrahamov-Kraft, Ethel; Yulevich, Alon; Sweed, Yechiel (European Journal of Pediatric Surgery, 2022)
Introduction The use of electric bicycles (EBs) among children younger than 18 years of age is rapidly increasing worldwide and becoming a substantial contributor to road accidents. We analyzed patterns and severity of pediatric bicycle-related injuries, comparing children riding EBs and classic bicycles (CBs).Materials and Methods This was a retrospective study (January 2016–December 2018) of patients arriving at our medical center due to a bicycle accident. Data were collected from medical records and included demographics, injury characteristics, treatment, and outcomes.Results Of 561 children, 197 (35%) were EB riders and 364 (65%) were CB riders. Injury severity score (ISS) of EB cyclists was significantly higher than CB cyclists (mean 4.08 ± 4.67 and 3.16 ± 2.84, respectively, p = 0.012). The rate of accidents involving motorized vehicles was higher in the EB versus CB group (25.9 vs. 11.3%, p < 0.001). Head injuries were the most common type of injury in both groups; incidence was higher in CB than in EB cyclists. However, loss of consciousness was more common in the EB group (18.3 and 12.1%, respectively, p = 0.057). Lower extremity injuries were more common in EBs versus CBs (55.8 and 37.6%, respectively, p < 0.001). Orthopaedic surgical interventions were significantly higher in the EB group (49.2 vs. 33.2%, p < 0.001), and length of stay in hospital and admission to pediatric intensive care unit were more common in EB compared with CB, although not significantly.Conclusion Injury severity of EB patients was significantly higher than that of CB patients. Accidents involving motorized vehicles were more common in the EB group. Head injury associated with loss of consciousness was significantly higher in EB patients.
Keywords: electric bicycles; classic bicycles; pediatric; trauma; bicycle injuries